Pharmacological inhibition of CDK4/6 impairs diffuse pleural mesothelioma 3D spheroid growth and reduces viability of cisplatin-resistant cells - Costa, Aurora; Forte, Iris Maria; Pentimalli, Francesca; Iannuzzi, Carmelina Antonella; Alfano, Luigi; Capone, Francesca; Camerlingo, Rosa; Calabrese, Alessandra; von Arx, Claudia; Benot Dominguez, Reyes; Quintiliani, Massimiliano; De Laurentiis, Michelino; et al. (Frontiers in Oncology, 2024)
Diffuse Pleural Mesothelioma (DPM) of the pleura is a highly aggressive and treatmentresistant cancer linked to asbestos exposure. Despite multimodal treatment, the prognosis for DPM patients remains very poor, with an average two years survival rate from diagnosis. Cisplatin, a platinum-based chemotherapy drug, is commonly used in the treatment of DPM. However, the development of resistance to cisplatin significantly limits its effectiveness, highlighting the urgent need for alternative therapeutic strategies. New selective inhibitors of cyclin-dependent kinases 4 and 6 (CDK4/6), have shown promise in various malignancies by inhibiting cell cycle progression and suppressing tumor growth. Recent studies have indicated the potential of abemaciclib for DPM therapy and a phase II clinical trial has shown preliminary encouraging results. Here, we tested abemaciclib, palbociclib and ribociclib on a panel of DPM cell lines and non-tumor mesothelial (MET-5A) cells. Specifically, we focused on abemaciclib which was the most effective cytotoxic agent on all the DPM cell lines tested. Abemaciclib reduced DPM cell viability, clonogenic potential, and ability to grow as 3D spheroids. In addition, abemaciclib induced prolonged effects, thereby impairing second generation Eliminato: Malignant 50